Nanostructured Zinc Oxide for Water Treatment - Baruah, Sunandan; K. Pal, Samir; Dutta, Joydeep (Nanoscience & Nanotechnology-Asia, 2012)
Environmental pollution and industrialization on a global scale have drawn attention to the vital need for developing new hygienically friendly purification technologies. Existing wastewater treatment technologies demand high capital investment and operation & maintenance cost, and large area. Cost-effective treatment of pollutants requires the transformation of hazardous substances into benign forms and the subsequent development of effective risk management strategies from harmful effects of pollutants that are highly toxic, persistent, and difficult to treat. Application of nanotechnology that results in improved water treatment options might include removal of the finest contaminants from water (< 300 nm) and “smart materials” or “reactive surface coatings” with engineered specificity to a certain pollutant that destroy, transform or immobilize toxic compounds. Nanomaterials have been gaining increasing interest in the area of environmental remediation mainly due to their enhanced surface and also other specific changes in their physical, chemical and biological properties that develop due to size effects. Heterogeneous photocatalytic systems via metal oxide semiconductors like TiO2 and ZnO, are capable of operating effectively and efficiently for waste water treatment which has been discussed along with other nanotechnology routes that can be useful for water treatments. Multifunctional photocatalytic membranes using ZnO nanostructures are considered advantageous over freely suspended nanoparticles due to the ease of its removal from the purified water. A short discussion on the study of charge transfer mechanisms during photocatalytic reactions has also been included.
Keywords: Contamination